Combustion characteristics of the direct injection diesel engine fuelled with corn oil methyl ester. Issue 2 (3rd March 2016) - SenthilKumar, R.; Loganathan, M.
Abstract : Petroleum-based fuels is a finite resource that is rapidly depleting. Consequently, petroleum reserves are not sufficient enough to last many years. In this research, an experimental investigation has been performed to give insight into the potential of biodiesel as an alternative fuel for direct injection (DI) diesel engines. The experimental work has been carried out to estimate the combustion characteristics of a single-cylinder, four-stroke, DI diesel engine fuelled with corn oil methyl ester (COME) and diesel blends. The COME was preheated to temperatures namely 50°C, 70°C and 90°C before it was supplied to the engine. The optimised preheated temperature of 70°C was chosen based on the higher brake thermal efficiency and lower specific fuel consumption. The performance, emission and combustion characteristics are evaluated by running the engine with COME and diesel blends at this preheated temperature. In this paper, the combustion characteristics are only discussed. The combustion characteristics such as ignition delay, maximum rate of pressure, heat release rate, cumulative heat release rate, mass fraction burned and combustion duration of COME methyl ester and diesel were evaluated and compared with neat diesel. The rate of pressure rise and maximum combustion pressure inside the cylinder were high for COME blends compared with neat diesel. The heat release rate of diesel is higher compared with COME blends. The ignition delay and combustion duration are decreased for COME blends compared with neat diesel. The cumulative heat release rate and mass fraction burnt of COME blends are higher than neat diesel.